Penggunaan Strategi Learning Start With A Question Dengan Question Student Have Terhadap Hasil Belajar Biologi Di Sekolah Menengah Pertama - leli Sri Nurhasanah Leli (EDU-BIO: Jurnal Pendidikan Biologi, 2018)
This research is a quasi-experimental research that aims to know the difference of learning outcomes between students who are given Learning Start with a Question Strategy with Question Student Strategy Have class VIII SMPN 1 Tungkal Jaya. The research design is posttest only control design. The population in this research is all students of class VIII SMPN 1 Tungkal Jaya of 3 classes. Sampling is done by cluster random sampling. Before the sample was determined, the initial homogeneity test was performed. After it was declared homogeneous, it was continued by lottery technique and obtained class VIII-1 as experiment-1 and class VIII-2 as experiment-2 class. Data of research result obtained by giving test result of learning at discussion of Digestive System, technique of data analysis by using t_test test. From the calculation results obtained t0 = 2.83 greater than ttable (either at a significant level of 5% or 1%), meaning null hypothesis (H0) rejected, so it can be concluded that the average learning outcomes Biology of students who treated strategy with Learning with a Question is better than the average of students’ Biology learning outcomes that are treated with the Question Student Have strategy. Keywords: Strategy, Learning Start with a Question, Question Student Have, Learning Outcomes